Pembelajaran Baca Tulis Alquran Dalam Dunia Pendidikan - Indiriani Tanjung, Indah; Nurhayati, Nurhayati; Jannah, Raudatul; Febriani Sari, Rina (Al-Ulum: Jurnal Pendidikan Islam, 2020)
The times are increasing both in technology and in education. Along with the development of the times, especially in the field of education, provisions that must be owned by educators and students not only in the field of education that is related to worldly, but education and knowledge about religion also become one of the things that are not very important in the world of education. Therefore, at this time the need for understanding educators and students towards reading and writing the Qur'an is increasing and increasing. Moreover, in this growing age, many people ignore the ability to read and write the Qur'an which is very important to learn. The demand for one's ability to be able to master the reading and writing of the Koran becomes one of the phenomena that has developed and spread in the world of education. Therefore, it is not only at the level of basic education that learns to read and write the Koran but at the university level especially for students who are in the Department of Teacher Education Madrasah Ibtidaiyah this is one of the lessons that must be mastered by students who later in life will become a prospective educator. Some things that must be understood are especially the understanding of reading and writing the Koran, the benefits of reading and writing the Koran, implementing reading and writing the Koran in the world of education, and others. Based on this, this paper will discuss related matters related to reading and writing the Koran in the world of education.Keywords: Read Write the Qur'an; BTQ learning; Education World